Ägypten: Industriearchitektur des 19. und 20. Jahrhunderts in Ägypten - Bodenstein, Ralph (e-Forschungsberichte des DAI, 2023)
The project on the history of industrial architecture in 19th and 20th century Egypt aims at exploring the historical development of Egypt‘s modern industrial architecture in its local and global context through field surveys and archival research. Project work during the years 2012–2013 focussed on the history and architecture of the sugar factories of Khedive Ismail, and on organising the international summer school „The former al-Ahram brewery in Cairo: Concepts for the reuse of a historical industrial building“.